ANALYSIS OF THE ACTIVITIES OF PRIESTS HEADED THE TASHKENT DIOCESE (Scientific journal of the Fergana State University, 2023)
The article analyzes the brief history of the penetration of the Christian religion into the Turkestan territory, the life of representatives of this religion after the occupation of the territory by Tsarist Russia, the activities of religious organizations, in particular the Tashkent diocese and the activities of the clergy headed by it.